KUALITAS PELAYANAN PERMOHONAN PASPOR RI PADA KANTOR IMIGRASI KELAS I SURAKARTA - Agus Setiadi (JI@P, 2016)
Service for the Republic of Indonesia Pasport is one of the public service givenby the Immigration Office becomes community interest issue. It is due to thatmany people’s desire have not been fullfilled. This research was aimed todescribe the quality of service for the Republic of Indonesia pasport in the Officeof Immigration Class I in Surakarta. Theory of Service Standard put foward byMahmudi was used for measuring the service provided by the Immigration OfficeClass I. The measurement of service standard mentioned are as: simplicity,clarity, timeliness, accuracy, safety, responsibility, completeness of means,accessability, discipline, politeness, hospitality, and comfortability. Qualitativeresearch approach was used in this study. Interview, and docoment studytechniques were employed to collect the needed data. Purposefull samplingtechnique was used to select the respondents. Respondents were theemployees who were incharge to serve pasport and the pasport applicants.Validity of the finding was supported by the data or resource triangulationmethod. Interactive analysis model consisting of three elements i.e. datareduction, data display, and verification and data conclusion was used to analysethe data. Research result indicated that the provided services by the office whichwere categorized as good were the aspects of simplicity, clarity, accuracy,safety, responsibility, accessability, discipline, politeness, hospitality, andcomfortability. On the other hand, aspect of timeliness was considered to be notgood, since the standard of service to publish the pasport supposed only fourwork-day, but in fact the time longer than six work-day. It was due to the troubleof the online system, in which the online system sometimes was offline. Aspectof completeness was evaluated bad since there was no enough parking lotspace and the absence of public toilet.Key words: Quality of service; simplicity, clarity; timeliness; accuracy; safety;responsibility; completeness of means; accessability; discipline;politeness; hospitality; and comfortability.